Performance of the scanning time in mobile worldwide interoperability for microwave access two threholds [electronic resource] - Nurzal Effiyana Ghazali, 1984-; Abu Sahmah Mohd. Supa'at; Sharifah Hafizah Syed Ariffin, supervisor; Fakulti Kejuruteraan Elektrik (2010)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2010